Digital badges on education: past, present and future - Araújo, Inês (2018)
Since the Roman Empire, badges are used as a symbol of a hierarchical position, as an accomplishment, or as a recognition of skill or interest. Throughout time they have been adapted to different contexts and needs. Nowadays, badges are used in different contexts, spaces (real and online) and with different purposes, but with the same aim: recognize something with value inside a community. In educational contexts, badges have been used to recognize skills mastering, achievements and in progress orientation. More recently, badges became digital and are used also to certify MOOC participation and to acknowledge soft skills, i.e. in not formal and informal learning experiences. Digital Badges have important characteristics that interest to education and employability. A badge is more than an image, as it represents a skill or experience that his/her owner has. It is also possible to see the evidence made by the owner to receive that badge and several data about or associated with the issuer. These features give credibility to digital badges’ issuing, and made them interesting to both education and recruitment fields. It is under these features and all its potential that projects like “Cities of Learning” in USA and “Open Badge Network” in EU emerged recently. A very important question is how badges can enhance education. For some authors and practitioners, badges can be used in continuing processes with employability aims. For others, its main benefit is related with motivational purposes inside the classroom. Today, as we search the Web, we can find different online tools for both aims. In this paper, we will describe the evolution of badges, the uses made in education and recent international projects that focus on the use of badges. Finally, we will put forward ways that can help teachers to use badges in their classrooms.